MATHEMATICAL MODEL AND DIFFERENTIAL EQUATION - MACUROVÁ, Anna (Trends in education, 2008)
The article introduces the result of the experimental dependencies of the maximum roughness of the cut surface. The maximum deviation is formulated by the differential equation.
Keywords: Roughness of the cut surface; differential equation.